A Sequence Type 23 Hypervirulent Klebsiella pneumoniae Strain Presenting Carbapenem Resistance by Acquiring an IncP1 blaKPC-2 Plasmid - Yan, Rushuang; Lu, Ye; Zhu, Yiwei; Lan, Peng; Jiang, Shengnan; Lu, Jun; Shen, Ping; Yu, Yunsong; Zhou, Jiancang; Jiang, Yan (Frontiers in Cellular and Infection Microbiology, 2021)
Hypervirulent Klebsiella pneumoniae strains are typically associated with severe infections and susceptible to most antimicrobial agents. In 2017, a carbapenem-resistant hypervirulent K. pneumoniae (CR-hvKP) strain was isolated from the sputum of a chronic obstructive pulmonary disease (COPD) patient in Zhejiang, China. The goal of the present study was to characterize the molecular features of the CR-hvKP isolate ZJ27003 and its blaKPC-2-harboring plasmid p27003_KPC. Antimicrobial susceptibility was evaluated using the broth microdilution and agar dilution methods. String tests, serum-killing and mouse survival assays were performed to assess virulence, and plasmid conjugation was performed by filter mating. The complete genome sequence of ZJ27003 was acquired using a hybrid assembly of Illumina and Nanopore platform data. The sequence type (ST) of this CR-hvKP isolate was identified as ST23, which exhibits hypervirulence with high serum resistance and murine infection model. The strain is also resistant to carbapenems (imipenem, meropenem and ertapenem), aztreonam and cephalosporins. Additionally, the CR-hvKP isolate carries a 36,708-bp blaKPC-2-harboring plasmid, named p27003_KPC, belonging to the P1 incompatibility (Inc) group. The backbone of p27003_KPC is similar to that of a blaGES-5-harboring Pseudomonas aeruginosa plasmid, in which the blaGES-5 and its surrounding regions were replaced by a blaKPC-2-containing translocatable unit derived from Enterobacteriaceae. The results of a conjugation assay revealed that p27003_KPC can be transferred from K. pneumoniae to P. aeruginosa PAO1 and make the recipient resistant against carbapenem. The identification of a carbapenem-resistant hypervirulent K. pneumoniae isolate carrying and disseminating the blaKPC-2 gene highlights a severe threat to public health.